Strengthening Teachers’ Role In Designing Gamification For Vocational School Learning - Siska, Jumiati; Yulianti, Liza; Kristiawan, Muhammad; Agustianza, Afes; Rinanda, Destika (International Journal of Public Devotion, 2026)
One innovative approach is gamification, which can improve student motivation, engagement, and learning outcomes. The problem when teachers don't implement gamification in the learning process primarily relates to their role in designing and integrating this strategy into vocational learning. Teachers need to be empowered to develop gamification designs that align with student characteristics and industry needs. This Community Service Program (PKM) aims to strengthen the role of teachers in designing gamification as a learning strategy in vocational schools. The scope of the research includes analyzing teacher needs, developing applicable gamification designs, and evaluating the effectiveness of gamification implementation in improving the quality of vocational learning. Data was obtained through observations, interviews, and questionnaires with vocational school teachers. The results of this PKM activity indicate that empowering teachers in designing gamification improves their creativity, pedagogical skills, and their ability to integrate technology into vocational learning. The implementation of gamification has been proven to increase student motivation, active engagement in the learning process, and optimal learning outcomes. In conclusion, strengthening the role of teachers in designing gamification is crucial for creating innovative learning strategies in vocational schools. Gamification not only increases student motivation and learning outcomes, but also empowers teachers to be more adaptive to developments in educational technology.Penguatan Peran Guru Dalam Merancang Gamifikasi Untuk Pembelajaran Di Sekolah KejuruanABSTRAKSalah satu pendekatan inovatif adalah gamifikasi, yang dapat meningkatkan motivasi, keterlibatan, dan hasil belajar siswa. Permasalahan ketika guru tidak mengimplementasikan gamifikasi pada proses pembelajaran, terutama terkait peran guru dalam merancang dan mengintegrasikan strategi tersebut ke dalam pembelajaran kejuruan. Guru perlu diberdayakan agar mampu mengembangkan desain gamifikasi yang sesuai dengan karakteristik peserta didik dan kebutuhan industri. PKM ini bertujuan untuk memperkuat peran guru dalam merancang gamifikasi sebagai strategi pembelajaran di sekolah kejuruan. Ruang lingkup penelitian meliputi analisis kebutuhan guru, pengembangan desain gamifikasi yang aplikatif, serta evaluasi efektivitas penerapan gamifikasi dalam meningkatkan kualitas pembelajaran kejuruan. Data diperoleh melalui observasi, wawancara, dan kuesioner kepada guru sekolah kejuruan. Hasil kegiatan PKM ini menunjukkan bahwa pemberdayaan guru dalam merancang gamifikasi meningkatkan kreativitas, keterampilan pedagogis, serta kemampuan mereka dalam mengintegrasikan teknologi ke dalam pembelajaran kejuruan. Penerapan gamifikasi terbukti mampu meningkatkan motivasi belajar siswa, keterlibatan aktif dalam proses pembelajaran, serta hasil belajar yang lebih optimal. Kesimpulan nya adalah bahwa penguatan peran guru dalam merancang gamifikasi sangat penting untuk menciptakan strategi pembelajaran yang inovatif di sekolah kejuruan. Gamifikasi tidak hanya meningkatkan motivasi dan hasil belajar siswa, tetapi juga memberdayakan guru untuk lebih adaptif terhadap perkembangan teknologi pendidikan.Kata Kunci :Peran guru; Pemberdayaan Guru; Gamifikasi; Desain pembelajaran; Sekolah kejuruan